Creating TV formats from inception to pitch - Miller, Catriona 1968-; Marshall, Hazel 1969-; Green, Linda 1973- (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2023)
"Creating TV Formats: from Inception to Pitch takes the reader through a step-by-step process of how to generate ideas, develop story lines and characters, and hook an audience, while staying aware of the realities of the media landscape. Beginning with a discussion about what a TV format is, each chapter then introduces a key aspect of the development process, such as looking for ideas, shaping the underlying story, and thinking about participants. Practical exercises guide the reader through each stage of turning an initial idea or subject matter into a hook or insight; the importance of incorporating storytelling principles; and techniques for designing and populating a story world. Examples from successful television formats such as First Dates and The Great British Bake Off are interwoven throughout the book alongside exclusive insights from the key industry professionals who brought them to the screen. From short form digital content to longer unscripted series, this is an essential guide to discovering and developing formats for any media or television production student or early career development professional"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Television authorship -- Vocational guidance -- Great Britain; Reality television programs -- Production and direction -- Vocational guidance -- Great Britain